Education as a Means and Effort to Increase Religious Tolerance in the Digital Era - Nurokhman, Nurokhman; Novanto, Riza Awal; Fariz, Ibnu As’ad Al; Inrawati, Lilis; Ikhtiari, Nila Akhsana; Rahma, Aolliya (Insan Akademika Publications, 2025)
In the digital age, any moment can be a lot of unexpected events. There is often opposition between people of different religions because many societies do not appreciate or understand these differences. This leads to intolerance that reflects ill effects. The study aims to instill knowledge and awareness in the harmony between individual believers through education, by improving the quality of religious tolerance primarily in human resources themselves. This type of study is a library research study. Data is collected from references to scientific articles: both primary, secondary, and auxiliary data, analyzing the content of the data obtained. Studies show that education is vitally important in improving religious tolerance efforts in the digital age. Education builds up religious tolerance marked by a difference in belief and belief. It is an essential effort to meet global challenges, so education is a strong foundation on which to create and improve the quality of religious tolerance. By understanding and appreciating differences, individuals can learn to appreciate one another and coexist peacefully. Hence, increased.